Nanoscale design of nano-sized particles in shape-memory polymer nanocomposites driven by electricity - Lu, Haibao (2013)
In the last few years, we have witnessed significant progress in developing high performance shape memory polymer (SMP) nanocomposites, in particular, for shape recovery activated by indirect heating in the presence of electricity, magnetism, light, radio frequency, microwave and radiation, etc. In this paper, we critically review recent findings in Joule heating of SMP nanocomposites incorporated with nanosized conductive electromagnetic particles by means of nanoscale control via applying an electro- and/or magnetic field. A few different nanoscale design principles to form one-/two-/three- dimensional conductive networks are discussed.